Preparation method of polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur battery, modified diaphragm and lithium-sulfur battery

By using polyacid to modify the covalent organic framework modified separator in lithium sulfur batteries, the problems of low conductivity, shuttle effect and short cycle life faced by lithium sulfur batteries in commercial applications are solved, and higher electrochemical performance and energy density are achieved.

CN119340604BActive Publication Date: 2025-04-15JILIN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411511443.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-04-15
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

In commercial applications, lithium-sulfur batteries face challenges such as low conductivity, shuttle effect of polysulfides, stability problems of electrolytes, short cycle life and poor structural stability, which limit their energy density, charge storage capacity and cycle stability.

Method used

The covalent organic framework (COF) modified separator is used to modify the separator. By synthesizing the DTQ-COF framework and adsorbing Keggin-type phosphotungstic acid (PW12) and phosphomolybdate (PMo12) are formed to form PW12/DTQ-COF and PMo12/DTQ-COF composite materials as modified separator materials to improve the electrochemical performance of lithium-sulfur batteries.

Benefits of technology

The modified separator significantly improves the conduction rate of lithium ions and the charging and discharging efficiency of the battery, inhibits the shuttle effect of polysulfides, and promotes the diffusion of Li+ through electrostatic action, improving the cycle stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340604B_ABST
    Figure CN119340604B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyacid-modified covalent organic skeleton modified diaphragm for a lithium-sulfur battery, a modified diaphragm and a lithium-sulfur battery, and belongs to the technical field of batteries. DTQ-COF solid powder is synthesized under the conditions that 2,6-diaminoanthraquinone and trialdehyde phloroglucinol are solutes, mesitylene and N,N-dimethylacetamide are mixed solvents, and acetic acid is used as a catalyst, and then Keggin-type phosphotungstic acid and phosphomolybdic acid are attached to the DTQ-COF skeleton by adsorption to obtain a composite material PW 12 / DTQ‑COF and PMo 12 / DTQ‑COF, and finally the two composite materials were mixed with PVDF and Super‑P in a defined ratio to prepare a modified diaphragm. 12 / DTQ‑COF and PMo 12 / DTQ‑COF has an ordered structure, which can increase the conductivity of lithium ions in the separator, thereby improving the charge and discharge efficiency of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a preparation method of a polyacid-modified covalent organic skeleton modified diaphragm for a lithium-sulfur battery, the modified diaphragm and a lithium-sulfur battery. Background Art

[0002] With the rapid development of advanced electronic devices, electric vehicles and smart grids, the demand for efficient and powerful energy storage devices (especially batteries) is increasing. Lithium-ion batteries (LIBs) have emerged as a popular energy storage device for their high energy density, excellent rate performance and long service life. However, LIBs technology is based on the lithiation-delithiation mechanism and uses insertion compounds as positive and negative electrode materials, which limits their energy density and charge storage capacity. In addition, the current commercial lithium-ion battery positive electrode materials are generally expensive, scarce or toxic. Therefore, it is crucial to develop new electrode materials that are abundant in resources and environmentally friendly.

[0003] Lithium-sulfur batteries (LSBs) have attracted widespread attention from academia and industry due to their high theoretical energy density of 2600 Wh / kg and ultra-high theoretical discharge capacity of 1675 mAh / g. However, despite their outstanding advantages, LSBs still face multiple challenges in commercial applications, mainly including the following aspects: (1) Low conductivity: The poor conductivity of sulfur leads to low electron conduction efficiency during the charge and discharge process of LSBs, which limits the power density and charging speed of the battery; (2) The "shuttle effect" of polysulfides: During the charge and discharge process, polysulfides (Li2S x , x = 1~8) will dissolve in the electrolyte, causing it to migrate between the positive and negative electrodes. This phenomenon not only reduces the energy efficiency of the battery, but may also lead to capacity decay and decreased cycle stability of the battery; (3) Electrolyte stability: The electrolyte of LSBs is easily decomposed under high voltage and high temperature conditions, resulting in decreased battery performance. In addition, the interaction between the electrolyte and polysulfides may affect the overall performance of the battery; (4) Short cycle life: Due to the dissolution and precipitation of polysulfides, LSBs are prone to capacity decay after multiple charge and discharge cycles, resulting in a short cycle life, which is an important obstacle to commercial applications; (5) Structural stability: The electrode material of LSBs undergoes volume changes during the charge and discharge process, which may lead to damage to the electrode structure and decreased battery performance.

[0004] In response to the current problems of LSBs, domestic and foreign scholars have optimized them from several angles, including the structure and composition of the positive electrode material, the optimization of the electrolyte, the modification of the separator material, and the optimization of the negative electrode / interface. Among them, the design and selection of the separator are crucial to the overall performance of the battery. Although traditional polymer separators have good mechanical strength and chemical stability, they have weak lithium ion conductivity and sulfur retention capacity. Therefore, it is particularly important to develop new multifunctional separator materials to achieve better battery performance. The best modified materials for the separator should have the characteristics of light weight, high catalytic activity, and high specific surface area. Covalent organic frameworks (COFs) have the advantages of clear structure, large specific surface area, periodic molecular arrangement, uniform pore distribution, and rich functional groups. They are ideal choices for separator modification materials. The COF material coated on the positive side of the separator not only acts as a physical barrier to prevent polysulfide from diffusing from the positive side to the negative side, but also further accelerates the transfer of electrons to the active material. This design strategy can not only suppress the “shuttle effect” of polysulfides and achieve long cycle life of LSBs, but also improve the electronic conductivity and utilization of active materials of the positive sulfur electrode.

[0005] Oxometalates (POMs) are referred to as polyoxoacids. There are a large number of terminal oxygens on their surfaces. The corner transition metal particles are very easy to produce vacancies and be replaced by other ions or functional groups, which can link other different ligands, maintain the stability of the original structure, and retain the characteristics of multiple atoms. Therefore, polyoxoacids have many advantages that traditional inorganic acids cannot match, such as good redox properties, high thermal stability, rich surface active groups, etc., and they show excellent performance in the field of electrochemistry. However, the poor conductivity, easy agglomeration and uneven dispersion of polyoxoacids limit their functions. Therefore, achieving a firm and uniform loading of polyoxoacids, exposing more active sites, and improving the conductivity and specific surface area of ​​polyoxoacids at the same time are the key to solving the application of polyoxoacids in the field of electrochemistry and energy storage systems. COFs are an ordered porous material containing light elements such as C, H, O, N, B and connected by covalent bonds. The combination of POMs and COFs materials is an important research direction that has emerged in recent years. Covalent organic frameworks (COFs) have the advantages of high porosity, large specific surface area and structural diversity. Polyacids can be easily adsorbed on their surfaces, thereby accelerating the adsorption and catalysis of lithium polysulfide by polyacid composites.

[0006] Defects and shortcomings of the existing technology:

[0007] The modification of lithium-sulfur batteries can be mainly divided into the following aspects: (1) Electrode material modification: by adding conductive agents (such as carbon nanotubes, graphene, etc.) to improve the conductivity of sulfur electrodes, thereby enhancing the efficiency of electronic conduction, or by compounding sulfur with conductive materials (such as carbon materials) to form composite electrodes to improve the conductivity and structural stability of the electrodes; (2) Electrolyte optimization: developing electrolytes with higher stability and better compatibility to reduce the dissolution of polysulfides and improve the cycle performance of batteries; (3) Improved functionalized diaphragms: by modifying the diaphragm (such as coating conductive materials or adding hydrophilic materials) to improve the conductivity of lithium ions and reduce the shuttle effect of polysulfides. Use porous materials as diaphragms to improve the conductivity efficiency of lithium ions and the overall performance of the battery; however, many modification methods involve multi-step synthesis processes, which increases the complexity of production. In addition, the price of the additives required for some diaphragm modification processes is relatively high, thereby increasing the manufacturing cost of the battery. At the same time, a certain degree of modification of the separator will have a certain impact on the lithium and sulfur transport speed, thereby restricting the performance of the battery. Some modifiers can cause problems such as battery safety and stability, such as thermal runaway and short circuit. Summary of the invention

[0008] In view of the problems existing in the prior art, the present application proposes a method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries, a modified diaphragm and a lithium-sulfur battery. An organic framework material (DTQ-COF) with abundant N / O functional groups inside the framework is synthesized using 2,6-diaminoanthraquinone and trialdehyde phloroglucinol as monomers, and then Keggin-type phosphotungstic acid (PW 12 ) and phosphomolybdic acid (PMo 12 ) were uniformly attached to the DTQ-COF skeleton to obtain the composite material PW 12 / DTQ-COF and PMo 12 / DTQ-COF, and use it as a modified diaphragm material to improve the electrochemical performance of lithium-sulfur batteries.

[0009] The method for preparing a polyacid-modified covalent organic framework modified diaphragm for a lithium-sulfur battery comprises the following steps:

[0010] S1. Synthesis of DTQ-COF

[0011] The solid powder after pretreatment of 2,6-diaminoanthraquinone (DAAQ) and trialdehyde phloroglucinol (TFP) is transferred to a Pyrex tube, and then a mixed solution of mesitylene and N,N-dimethylacetamide is added to the Pyrex tube, and ultrasonic vibration is performed for 1-5 minutes to uniformly mix the solid powder and the mixed solution, and then acetic acid is added to continue ultrasonic vibration for 1-2 minutes; then the Pyrex tube is frozen and vacuumed three times, flame-sealed with butane gas, and heated to obtain a brown-yellow powder solid product; it is washed with an acetone solution for 3-5 times by high-speed centrifugation until the color of the washing liquid is clear; the washed solid product is vacuum dried to obtain a brown-yellow solid powder DTQ-COF;

[0012] The pretreatment is specifically as follows: 2,6-diaminoanthraquinone (DAAQ) and trialdehyde phloroglucinol (TFP) are mixed and ground for 1-1.5 min, then 3-5 drops of ethanol are added, and the mixture is ground again for 1-1.5 min to obtain a solid powder;

[0013] S2. Preparation of PW 12 / DTQ-COF and PMo 12 / DTQ-COF

[0014] Keggin type phosphotungstic acid (PW 12 ) or Keggin-type phosphomolybdic acid (PMo 12 ) was stirred and dissolved in anhydrous ethanol to obtain phosphotungstic acid (PW 12 ) or phosphomolybdic acid (PMo 12 ) ethanol solution, then dissolve DTQ-COF in the above solution, stir for 20-24 h and filter, and vacuum dry the solid obtained after filtration to obtain

[0015] PW 12 / DTQ-COF or PMo 12 / DTQ-COF;

[0016] S3. Preparation of modified diaphragm

[0017] (1) Dry grinding: PW 12 / DTQ-COF or PMo 12 / DTQ-COF was mixed with PVDF and Super-P, respectively, and the mixture was obtained after ball milling;

[0018] (2) Wet grinding: Add NMP solution to the mixture and ball mill for 1-2 h to obtain a slurry;

[0019] (3) The slurry is evenly coated on the PP surface using a 40-50 mm four-sided sampler, and then vacuum dried to obtain a diaphragm;

[0020] (4) The diaphragm was cut into discs with a diameter of 16 mm to obtain a modified diaphragm.

[0021] The molar ratio of 2,6-diaminoanthraquinone and trialdehyde phloroglucinol in step S1 is 8:(5-6);

[0022] The volume ratio of mesitylene to N,N-dimethylacetamide in step S1 is 1:(2-4);

[0023] The usage ratio of 2,6-diaminoanthraquinone and N,N-dimethylacetamide in step S1 is: (15-20) mg: (0.3-0.6) ml;

[0024] The concentration of acetic acid in step S1 is 6 mol / L, and the amount of acetic acid used is 0.1-0.4 ml;

[0025] The heating time in step S1 is 100-150 h, and the heating temperature is 100-150 °C;

[0026] The Keggin type phosphotungstic acid (PW 12 ) or Keggin-type phosphomolybdic acid (PMo 12 The ratio of the mass of ) to the mass of DTQ-COF is (1-2): 10;

[0027] In step S3 (1), the PW 12 / DTQ-COF or PMo 12 / DTQ-COF), the mass ratio of PVDF and Super-P is 6:1:3;

[0028] The ball milling time in step S3 (1) is 1-1.5 h;

[0029] The vacuum drying temperature in all the above steps is 80-100°C and the drying time is 12-24 h;

[0030] A modified diaphragm is prepared by adopting the preparation method of the polyacid-modified covalent organic skeleton modified diaphragm for lithium-sulfur battery.

[0031] A lithium-sulfur battery comprises a polyacid-modified covalent organic skeleton modified diaphragm for a lithium-sulfur battery obtained by the above preparation method.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1. The solution of the present invention adopts a solvothermal method to synthesize a covalent organic framework DTQ-COF, and through adsorption, Keggin type phosphotungstic acid (PW 12 ) and phosphomolybdic acid (PMo 12) were uniformly attached to the DTQ-COF skeleton to obtain the composite material PW 12 / DTQ-COF and PMo 12 / DTQ-COF, and use it as a modified diaphragm material to improve the electrochemical performance of lithium-sulfur batteries.

[0034] 2. PW 12 / DTQ-COF, PMo 12 / DTQ-COF has an ordered structure, which can improve the conductivity of lithium ions in the separator, thereby improving the charge and discharge efficiency of the battery. In addition, due to the presence of polyacid clusters in the structure, PW 12 / DTQ-COF / PMo 12 / DTQ-COF modified intermediate layer assembled battery has higher ionic conductivity; in addition, based on PW 12 / DTQ-COF / PMo 12 The modified interlayer of DTQ-COF can not only inhibit

[0035] The shuttling of polysulfides can also promote the Li + Diffusion of PW 12 / DTQ-COF / PMo 12 The / DTQ-COF battery also exhibited excellent electrochemical performance, with an initial specific capacity of 863.4 mAh·g at 1 C. -1 The specific capacity after 500 cycles is 579.9 mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the synthesis process of the polymer DTQ-COF of the present invention;

[0037] Figure 2 The XRD diagrams of the polymers obtained in Examples 1, 4 and 6 of the present invention are shown in FIG. Figure 2 (a) is the PXRD pattern of DTQ-COF. Figure 2 (b) PW 12 / DTQ-COF and PMo 12 PXRD spectrum of / DTQ-COF;

[0038] Figure 3 The nitrogen adsorption-desorption analysis and pore size distribution diagram of the polymers obtained in Examples 1, 4 and 6 of the present invention are shown in FIG. Figure 3 (a) PW 12 / DTQ-COF、PMo 12 / DTQ-COF and N2 adsorption-desorption isotherms of DTQ-COF, Figure 3(b) PW 12 / DTQ-COF、PMo 12 / DTQ-COF and DTQ-COF pore size distribution diagram;

[0039] Figure 4 The XPS graphs of the polymers obtained in Examples 1 and 4 of the present invention are shown in FIG. Figure 4 (a) X-ray photoelectron spectrum of DTQ-COF; Figure 4 (b) C1s spectrum of DTQ-COF; Figure 4 (c) N 1s spectrum of DTQ-COF; Figure 4 (d) O 1s spectrum of DTQ-COF.

[0040] Figure 5 This is a high-resolution scanning electron microscope image of the polymer obtained in Example 6 of the present invention, wherein: Figure 5 (a) PW 12 / SEM image of DTQ-COF membrane, Figure 5 (b) is polymer PMo 12 / SEM image of DTQ-COF membrane; Figure 5 (c) is a scanning electron microscope image of the polymer DTQ-COF membrane; Figure 5 (d) PW 12 / DTQ-COF、PMo 12 / DTQ-COF separator and bending test of DTQ-COF separator;

[0041] Figure 6 This is a performance diagram of the Li-S battery prepared by the present invention, wherein: Figure 6 (a) PW 12 / DTQ-COF, PMo 12 / CV diagrams of DTQ-COF and DTQ-COF battery; Figure 6 (b) PW 12 / DTQ-COF, PMo 12 / DTQ-COF and DTQ-COF conductivity diagram; Figure 6 (c) PW 12 / DTQ-COF, PMo 12 / DTQ-COF and DTQ-COF conductivity bar graph; Figure 6 (d) PW 12 / DTQ-COF, PMo 12 / EIS graphs of DTQ-COF and DTQ-COF battery; Figure 6 (e) is PW 12 / Lithium ion migration number diagram of DTQ-COF battery; Figure 6 (f) is PMo12 / Lithium ion migration number diagram of DTQ-COF battery; Figure 6 (g) is PMo 12 / Lithium ion migration number diagram of DTQ-COF battery; Figure 6 (h) is PW 12 / DTQ-COF, PMo 12 / Rate performance diagram of DTQ-COF and DTQ-COF modified batteries; Figure 6 (i) PW 12 Discharge-charge curves of / DTQ-COF modified batteries at different current densities of 0.1, 0.2, 0.5, 1, and 2 C; Figure 6 (j) is PMo 12 Discharge-charge curves of / DTQ-COF modified batteries at different current densities of 0.1, 0.2, 0.5, 1, and 2 C; Figure 6 (k) is the discharge-charge curve of DTQ-COF modified battery at different current densities of 0.1, 0.2, 0.5, 1 and 2 C; Figure 6 (l) is PW 12 / DTQ-COF, PMo 12 / 500 long cycle performance diagram of DTQ-COF and DTQ-COF modified batteries at 1 C;

[0042] Figure 7 PW obtained in Example 8 12 / DTQ-COF, PMo 12 Small magnification scanning electron microscopy images of modified diaphragms prepared by / DTQ-COF and DTQ-COF;

[0043] Figure 8 This is a scanning electron microscope image of the modified diaphragm of Comparative Example 1;

[0044] Fig. 9 This is a scanning electron microscope image of the modified diaphragm of Comparative Example 2;

[0045] Fig.10 This is the scanning electron microscope image of the modified diaphragm of comparative example 3. DETAILED DESCRIPTION

[0046] The following will clearly and completely describe the concept of the present invention and the technical effects produced in combination with the embodiments and drawings, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0047] The present invention is further described below in conjunction with the embodiments. The instruments and equipment used in the embodiments of the present invention and their models are: Shanghai Chenhua electrochemical workstation (Chenhua CHI660E) and Blue Electric Battery Test System (CT2001A).

[0048] Measured Li-S battery in the voltage range of 1.7-2.8 V, 0.1 mV·s -1 Cyclic voltammetry curves at . Electrochemical impedance spectroscopy, the cycling stability at 1 C and the rate performance of Li-S batteries at different current densities were measured on a Blue Battery Test System (CT2001A).

[0049] The assembly process of the Li-S battery of the present invention comprises the following steps:

[0050] 1. Preparation of C / S composites

[0051] The C / S composite material was prepared using the traditional melt diffusion method. First, Super-P powder and sulfur powder in a mass ratio of 2.5:7.5 were mixed and fully ground in a mortar. Then, the mixture was placed in a polytetrafluoroethylene-lined reactor and heated at 155 °C for 24 h under an argon protection atmosphere. Finally, the product was collected after cooling to room temperature to obtain the C / S composite material.

[0052] 2. Preparation of conventional positive electrode

[0053] The C / S composite material, carbon black and PVDF with a mass ratio of 8:1:1 were mixed and ground evenly, and then 1-methyl-2-pyrrolidone (NMP) was added and stirred thoroughly to form a uniform slurry. The slurry was evenly coated on the aluminum foil using a coater and then dried at 60 °C for 24 h. After drying, the aluminum foil was cut into circular electrodes using a slicer to obtain the desired electrode.

[0054] 3. Battery Assembly

[0055] Before assembly, prepare all battery-related components. CR2023 button cells were selected as the battery model; commercial metal lithium sheets with a diameter of 16 mm were used as electrodes; the electrolyte consisted of a DOL / DME mixture of 1 wt% LiNO3 and 1 M LiTFSI, with a DOL / DME volume fraction of 1:1; the prepared modified film was cut into diaphragm discs with a diameter of 16 mm.

[0056] The assembly of button cells must be carried out in an argon glove box to ensure that the moisture and oxygen content in the glove box are less than 1 ppm. The assembly steps are as follows: first, place the prepared sulfur cathode material into the cathode shell; then drip an appropriate amount of electrolyte on the surface of the sulfur cathode, with a molar ratio of 24 μL·mg to sulfur. -1Then, add the cut diaphragm, and drip 40 μL of electrolyte on it again, and then put in the metal lithium sheet; in addition, add stainless steel gaskets, springs and negative electrode shells, and finally, use a button battery packaging machine to package it. After packaging, let it stand for 24 hours to facilitate subsequent testing.

[0057] Example 1

[0058] Synthesis of DTQ-COF

[0059] 17 mg of 2,6-diaminoanthraquinone (DAAQ) and 10 mg of trialdehyde pyrogallol (TFP) were mixed and poured into a mortar. After grinding for 1 min, 3 drops of ethanol were added using a rubber-tipped dropper and ground again for 1 min. At this time, the solid powder was observed to change from reddish brown to orange. The solid powder was transferred to a 5 ml Pyrex tube, and then 0.6 ml of a solution of mesitylene and N,N-dimethylacetamide was mixed in a volume ratio of 1:3 and added to the Pyrex tube. Ultrasonic vibration was performed for 4 min to evenly mix the above monomers, and then 6 mol / L, 0.2 ml of acetic acid was added and ultrasonic vibration was continued for 1 min. After that, the Pyrex tube was frozen and vacuumed three times, flame-sealed with butane gas, and heated at 120 °C for 120 h to obtain a brown-yellow powder solid product. Next, it was washed three times with acetone solution by high-speed centrifugation until the color of the washing solution became clear. The washed solid was placed in a vacuum drying oven at 80 °C and dried for 12 h to obtain a brown-yellow solid DTQ-COF with a yield of 76 %; The schematic diagram of the synthesis process of DTQ-COF is as follows Figure 1 shown.

[0060] Example 2

[0061] Synthesis of DTQ-COF

[0062] 34 mg of 2,6-diaminoanthraquinone (DAAQ) and 20 mg of trialdehyde pyrogallol (TFP) were mixed and poured into a mortar. After grinding for 1.5 min, 5 drops of ethanol were added using a rubber-tipped dropper and ground again for 1 min. At this time, the solid powder was observed to change from reddish brown to orange. The solid powder was transferred to a 10 ml Pyrex tube, and then 1.2 ml of a solution of mesitylene and N,N-dimethylacetamide was mixed in a volume ratio of 1:4 and added to the Pyrex tube. Ultrasonic vibration was performed for 5 min to evenly mix the above monomers, and then 6 mol / L, 0.4 ml of acetic acid was added and ultrasonic vibration was continued for 2 min. After that, the Pyrex tube was frozen and vacuumed three times, flame-sealed with butane gas, and heated at 100 °C for 144 h to obtain a brown-yellow powder solid product. Next, it was washed with acetone solution by high-speed centrifugation for 5 times until the color of the washing solution became clear. The washed solid sample was placed in a vacuum drying oven at 100 °C for 16 h, and finally a brown-yellow solid DTQ-COF was obtained with a yield of 70.5%.

[0063] Example 3

[0064] Synthesis of DTQ-COF

[0065] Mix 51 mg of 2,6-diaminoanthraquinone (DAAQ) and 10 mg of trialdehyde phloroglucinol (TFP) in a mortar, grind for 1 min, add 4 drops of ethanol using a rubber-tipped dropper, grind again for 1.5 min, and then observe that the solid changes from reddish brown to orange. Put the treated solid powder into a 10 ml Pyrex tube, then mix mesitylene and N,N-dimethylacetamide in a volume ratio of 1:2 to make a 1.8 ml solution and add it to the Pyrex tube. Ultrasonic vibration for 4 min to evenly mix the above monomers, then add 6 mol / L, 0.6 ml acetic acid and continue ultrasonic vibration for 1 min. After that, the Pyrex tube was frozen and vacuumed three times, flame-sealed with butane gas, and heated at 150 ° C for 100 h to obtain a brown-yellow powder solid product. Next, it was washed 5 times with acetone solution by high-speed centrifugation until the color of the washing liquid became clear. The washed solid sample was placed in a vacuum drying oven at 95 °C and dried for 20 h to obtain brown solid DTQ-COF with a yield of 68.1%.

[0066] Example 4

[0067] Preparation of PW 12 / DTQ-COF

[0068] Take 20 mg of Keggin-type phosphotungstic acid (PW 12) was stirred and dissolved in 50 ml of anhydrous ethanol, and 200 mg of DTQ-COF prepared in Example 1 was dissolved in the above ethanol solution, stirred for 24 h and then filtered, and the obtained solid was dried at 80 ° C for 12 h to obtain PW 12 / DTQ-COF.

[0069] Example 5

[0070] Preparation of PW 12 / DTQ-COF

[0071] Take 10 mg of Keggin-type phosphotungstic acid (PW 12 ) was stirred and dissolved in 50 ml of anhydrous ethanol, and 50 mg of DTQ-COF prepared in Example 1 was dissolved in the above ethanol solution, stirred for 20 h and then filtered, and the obtained solid was dried at 90 ° C for 16 h to obtain PW 12 / DTQ-COF.

[0072] Example 6

[0073] Preparation of PMo 12 / DTQ-COF

[0074] 20 mg of Keggin-type phosphomolybdic acid (PMo 12 ) was stirred and dissolved in 50 ml of anhydrous ethanol, and 200 mg of DTQ-COF prepared in Example 1 was dissolved in the above ethanol solution, stirred for 24 h and then filtered, and the obtained solid was dried at 80 ° C for 12 h to obtain PMo 12 / DTQ-COF.

[0075] Example 7

[0076] 10 mg of Keggin-type phosphomolybdic acid (PMo 12 ) was stirred and dissolved in 50 ml of anhydrous ethanol, and 100 mg of DTQ-COF prepared in Example 1 was dissolved in the above ethanol solution, stirred for 24 h and then filtered, and the obtained solid was dried at 80 ° C for 12 h to obtain PMo 12 / DTQ-COF.

[0077] The DTQ-COF powder obtained in Example 1 and the PW prepared in Example 4 12 / DTQ-COF and PMo prepared in Example 6 12 The X-ray diffraction pattern (XRD) of / DTQ-COF is as follows Figure 2As shown, the XRD pattern of DTQ-COF shows that the diffraction peaks are located at 3.3°, 5.95°, 7.03° and 26.86°, which correspond to the (100) and (110), (210) and (001) crystal planes of the material, respectively. Figure 2 a), PW was further analyzed by powder XRD pattern 12 / DTQ-COF and PMo 12 / DTQ-COF, the XRD diffraction peak of DTQ-COF in the composite material still exists, which further proves that DTQ-COF can still maintain its structural order after polyacid loading, and the peak shape is consistent with the original DTQ-COF; 12 / DTQ-COF and PMo 12 No PW was observed in the DTQ-COF composites. 12 and PMo 12 The typical diffraction peaks of , indicating that the polyacid clusters have no agglomeration and are uniformly dispersed on the hollow DTQ-COF ( Figure 2 b).

[0078] The DTQ-COF powder obtained in Example 1 and the PW prepared in Example 4 12 / DTQ-COF and PMo prepared in Example 6 12 N2 adsorption experiment of / DTQ-COF at 77 K Figure 3 As shown in Figure 3a, the N2 adsorption isotherm shows that compared with DTQ-COF (278.72 m 2 ·g -1 ), the specific surface areas of the composite materials PW12 / DTQ-COF and PMo12 / DTQ-COF increased significantly after the introduction of POMs modification; according to the IUPAC classification, the three materials all follow the characteristics of type I reversible adsorption curves and have microporous structures; PW12 / DTQ-COF (1218.9m 2 ·g -1 ) and PMo12 / DTQ-COF (1078.1 m 2 ·g -1 ) are larger than DTQ-COF (278.72 m 2 ·g -1 ), the larger specific surface area can not only effectively accelerate the transfer of electrons during the cycle, but also provide a more active pathway for the adsorption and conversion of lithium polysulfide. The non-local density functional theory (NLDFT) method estimated the pore size and pore size distribution of these three materials. Their pore sizes are mainly concentrated in 1-3 nm, which further proves that they are microporous materials ( Figure 3 b).

[0079] X-ray photoelectron spectrum of the DTQ-COF powder obtained in Example 1. The DTQ-COF material contains C, O and N elements. Through further high-resolution XPS fitting spectrum analysis of the DTQ-COF material, the C 1s spectrum is decomposed into three peaks with binding energies of 284.68, 287.88 and 286.38 eV, respectively, belonging to C=C, CN and C=O, respectively. The N 1s spectrum is decomposed into two peaks with binding energies of 399.58 and 400.08 eV, respectively, belonging to CN and -NH2, respectively. The O 1s spectrum is decomposed into two peaks with binding energies of 531.18 and 532.88 eV, respectively, belonging to C=O and CO, as shown in Figure 1. Figure 4 This result demonstrates the successful preparation of DTQ-COF.

[0080] Example 8

[0081] Preparation of modified diaphragm

[0082] (1) Dry grinding: PW 12 / DTQ-COF、PMo 12 / DTQ-COF and DTQ-COF were mixed with PVDF and Super-P, respectively, and ball-milled for 1 h to obtain a mixture;

[0083] (2) Wet grinding: Add NMP solution to the mixture and ball mill for 1.5 h to obtain a slurry;

[0084] (3) The slurry was evenly coated on the PP surface using a 40 mm four-sided sampler, and then vacuum dried to obtain a diaphragm;

[0085] (4) The diaphragm was cut into discs with a diameter of 16 mm to obtain a modified diaphragm.

[0086] Figure 5 PW prepared in Example 8 12 / DTQ-COF, PMo 12 Figures 5a, 5b and 5c show the high-resolution scanning electron microscopy images of PW / DTQ-COF and DTQ-COF modified membranes. 12 / DTQ-COF, PMo 12 SEM images of the DTQ-COF / DTQ-COF and DTQ-COF modified diaphragms. It can be seen that the three composite diaphragms have completely covered the voids of the original PP diaphragm. 12 / DTQ-COF, PMo 12 / DTQ-COF and DTQ-COF adhesion strength on PP separator, PW 12 / DTQ-COF, PMo 12 / DTQ-COF and DTQ-COF modified separators were subjected to bending tests. Figure 5 As can be seen in Figure d, the diaphragm did not have any creases after being folded, and it completely recovered to its original shape, and no powder was found to fall off, which indicates that the diaphragm prepared by this method has good bending strength.

[0087] from Figure 7 It can be seen that after scanning with a small scanning electron microscope, PW 12 / DTQ-COF modified diaphragm has the smallest cracking. The smaller the cracking, the more uniform the coating of the diaphragm material and the better the effect.

[0088] Comparative Example 1

[0089] (1) Dry grinding: PW 12 / DTQ-COF、PMo 12 / DTQ-COF and DTQ-COF were mixed with PVDF and Super-P at a weight ratio of 7:1:2, respectively, and ball-milled for 1 h;

[0090] (2) Wet grinding: Add NMP solution to the mixture ground in the previous step and ball mill for 1.5 h to obtain a slurry.

[0091] (3) The mixed slurry was evenly coated on the PP surface using a 40 mm four-sided sampler, and then placed in a vacuum oven at 60 °C for 12 h;

[0092] (4) The diaphragm obtained in the previous step was cut into discs with a diameter of 16 mm, which was the modified diaphragm. The scanning electron microscope image of the modified diaphragm was shown in FIG. Figure 8 shown.

[0093] Comparative Example 2

[0094] (1) Dry grinding: PW 12 / DTQ-COF、PMo 12 / DTQ-COF and DTQ-COF were mixed with PVDF and Super-P at a weight ratio of 5:1:4, respectively, and ball-milled for 1 h;

[0095] (2) Wet grinding: Add NMP solution to the mixture ground in the previous step and ball mill for 1.5 h to obtain a slurry;

[0096] (3) The mixed slurry was evenly coated on the PP surface using a 40 mm four-sided sampler, and then placed in a vacuum oven at 60 °C for 12 h;

[0097] (4) The diaphragm obtained in the previous step was cut into discs with a diameter of 16 mm, which was the modified diaphragm. The scanning electron microscope image of the modified diaphragm was shown in FIG. Fig. 9 shown.

[0098] Comparative Example 3

[0099] (1) Dry grinding: PW 12 / DTQ-COF、PMo 12 / DTQ-COF and DTQ-COF were mixed with PVDF and Super-P at a weight ratio of 4:1:5, respectively, and ball-milled for 1 h;

[0100] (2) Wet grinding: Add NMP solution to the mixture ground in the previous step and ball mill for 1.5 h to obtain a slurry;

[0101] (3) The mixed slurry was evenly coated on the PP surface using a 40 mm four-sided sampler, and then placed in a vacuum oven at 60 °C for 12 h;

[0102] (4) The diaphragm obtained in the previous step was cut into discs with a diameter of 16 mm, which was the modified diaphragm. The scanning electron microscope image of the modified diaphragm was shown in FIG. Fig.10 shown.

[0103] It can be seen from the above Example 8 and Comparative Examples 1-3 that adjusting PW 12 / DTQ-COF、 PMo 12 / DTQ-COF and the ratio of DTQ-COF to PVDF and Super-P were different. 12 / DTQ-COF、PMo 12 When / DTQ-COF and DTQ-COF are mixed with PVDF and Super-P in a weight ratio of 6:1:3, the prepared separators have relatively better flatness and the degree of cracking is minimal.

[0104] Assembling Li-S batteries

[0105] 1. Preparation of C / S composites

[0106] The C / S composite material was prepared using the traditional melt diffusion method. First, Super-P powder and sulfur powder in a mass ratio of 2.5:7.5 were mixed and fully ground in a mortar. Then, the mixture was placed in a polytetrafluoroethylene-lined reactor and heated at 155 °C for 24 h under an argon protection atmosphere. Finally, the product was collected after cooling to room temperature to obtain a C / S composite material.

[0107] 2. Preparation of conventional positive electrode

[0108] 80% by mass of the C / S composite material prepared above, 10% by mass of carbon black and 10% by mass of PVDF were fully mixed and ground uniformly; subsequently, 1-methyl-2-pyrrolidone (NMP) was added and stirred thoroughly to ensure the formation of a uniform slurry; the slurry was evenly coated on an aluminum foil using a coater and then dried at 60 °C for 24 h; after drying, the aluminum foil was cut into circular electrodes using a slicer to obtain the desired electrode.

[0109] 3. Battery Assembly

[0110] Before assembly, prepare all battery-related components; select CR2025 button cell as the battery model; use commercial metal lithium sheet with a diameter of 16 mm as the electrode, and the electrolyte is composed of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) with a volume fraction of 1:1 as solvent, 1 wt% LiNO3 and 1 M LiTFSI as solute; PW prepared in Example 8 12 / DTQ-COF、PMo 12 / DTQ-COF and DTQ-COF modified separators were cut into 16 mm diameter pieces as separator discs.

[0111] The assembly of button cells needs to be carried out in an argon glove box to ensure that the moisture and oxygen content in the glove box are less than 1 ppm. The assembly steps are as follows: first, the prepared sulfur cathode material is placed in the cathode shell, and then the electrolyte is dripped on the surface of the sulfur cathode, and the electrolyte and sulfur molar ratio is 24 μL·mg -1 , then add the cut diaphragm disc, and drip 40μL of electrolyte on it again, then put in the metal lithium sheet, in addition, add stainless steel gasket, shrapnel and negative electrode shell; finally, use button battery packaging machine for packaging, and let it stand for 24 hours after packaging for subsequent testing.

[0112] In order to study the electron transfer kinetics between redox products and electrodes, the performance of polymer batteries was analyzed, such as Figure 6 As shown, in the potential range of 1.7 to 2.8 V, the -1 The CV curves of batteries with different separators were measured at a scan rate of Figure 6 As shown in (a), in the first cycle of the CV curve, the three materials all showed obvious reduction peaks and oxidation peaks, and maintained good repeatability within 5 cycles, which shows that the three membranes have excellent stability; PW 12 The lithium-sulfur battery with / DTQ-COF separator shows two reduction peaks at 2.01 V and 2.29 V, corresponding to the conversion of S to Li2S x(x = 4-8) and further generate solid Li2S2 / Li2S. The two oxidation peaks around 2.36 V and 2.44 V are respectively attributed to the conversion of Li2S2 / Li2S to Li2S x (x=4-8) and finally converted to S. By comparing the CV graphs of these three materials, it can be found that 12 / DTQ-COF and PMo 12 The CV curve of the battery assembled with / DTQ-COF shows a trend of rightward shift of reduction peak and leftward shift of oxidation peak. 12 The polarization voltage of DTQ-COF battery (0.35 V) is greater than that of PMo 12 The polarization voltages of DTQ-COF (0.38 V) and DTQ-COF (0.42 V) are Figure 6 a). Electrochemical impedance spectroscopy (EIS) was used to further evaluate the Li + The conductivity of PW at 25 °C (frequency range: 1-105 Hz; amplitude voltage: 20 mV). 12 / DTQ-COF and PMo 12 / DTQ-COF Li + The conductivity is 2.81 and 2.34 mS·cm respectively. -1 , which is better than DTQ-COF (2.11 mS·cm -1 )( Figure 6 b, 6 c). This result shows that the composite material PW containing polyacid 12 / DTQ-COF and PMo 12 / DTQ-COF as a separator for Li + The penetration has better selectivity.

[0113] In order to gain a deeper understanding of the excellent performance of the battery, an EIS test was conducted to test the electrochemical impedance spectroscopy (EIS) of LSBs assembled with different separators. From the EIS of the three batteries, it can be seen that among the three separators, the PW12 / DTQ-COF separator shows the smallest semicircular diameter in the Nyquist spectrum. Compared with the charge transfer resistance Rct (about 80) of the DTQ-COF separator modified battery, the PW 12 / DTQ-COF (about 57) and PMo 12 / DTQ-COF (about 70) has a smaller charge transfer resistance ( Figure 6 d). These results indicate that the strategy of confining polyacid clusters through porous materials DTQ-COF can reduce the resistance of the battery, facilitate the rapid migration of lithium ions, and improve the electrochemical activity. + Transfer number (t +) is measured by constant potential polarization method. The It curves and Nyquist curves of the three batteries before and after repolarization are shown in Figure xx. Li + The migration number is only 0.90, while PW 12 Li / DTQ-COF and PMo12 / DTQ-COF + The migration numbers are 0.93 and 0.91 respectively. + The increase in the migration number may be due to the introduction of POMs, which repels polysulfides and promotes Li + Migration ( Figure 6 eg).

[0114] By further evaluating the rate performance tests of the three materials, such as Figure 6 As shown, it can be seen that the composite material PW 12 / DTQ-COF exhibits 1084.1, 956.6, 846.9, 782, and 550.6 mA h·g at current densities of 0.1, 0.2, 0.5, 1, and 2 C, respectively. -1 The initial discharge capacity of the composite material PMo 12 The initial discharge specific capacities of / DTQ-COF are 1006.2, 925.2, 782.6, 725.2, and 515.2 mA h·g -1 , compared with the original DTQ-COF, PW 12 / DTQ-COF and PMo 12 The capacities of the batteries modified with the / DTQ-COF separators are all improved. At the same rate, the initial capacities of the DTQ-COF are 924.9, 754.9, 699.7, 665.9 and 476.9 mA·h·g, respectively. -1 ( Figure 6 h); PW 12 / DTQ-COF, PMo 12 The constant current charge-discharge curves of the battery assembled with / DTQ-COF and DTQ-COF and separator show that when the current density increases from 0.1 C to 2 C, the two typical charge-discharge platforms of the sulfur cathode can still be clearly seen ( Figure 6 ik), which shows that the material has good stability and reversibility. In addition, PW 12 The / DTQ-COF composite material exhibited the highest discharge specific capacity (initial 863.4 mA·g -1 , 500 cycles, 579.9 mA·h·g -1 , the decay rate per cycle is only 0.066%), while the DTQ-COF as a comparative sample has a smaller specific capacity (initial 741.1 mA·g -1, 500 cycles, 243.5 mA·h·g -1 , the decay rate per cycle is only 0.13%). 12 The initial discharge capacity of / DTQ-COF is 796.6 mA·g -1 , after 500 cycles, it becomes 500.9 mA·h·g -1 The decay rate of each cycle is only 0.074%. Obviously, the composite material PW modified by POMs 12 / DTQ-COF and PMo 12 / DTQ-COF separator has higher reversible capacity than DTQ-COF ( Figure 6 l), which proves that PW 12 and PMo 12 The contribution of components to the electrochemical performance of lithium-sulfur batteries. The enhancement of electrochemical performance is the result of PW 12 / DTQ-COF and PMo 12 / DTQ-COF composites for PW 12 and PMo 12 This is due to the confinement strategy, which can alleviate the dissolution of polyacids in the electrolyte and reduce the 12 and PMo 12 reunion.

[0115] The above embodiments are only partial implementation schemes of the present invention, but the protection scope of the present invention is not limited thereto. The various aspects and implementation schemes of the present invention disclosed herein are only examples of specific ways to make and use the present invention. The present invention is not limited to any limitation due to the sequence and specific operations of the embodiments. Any replacement and changes that can be easily thought of by any researcher familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries, characterized in that: The following steps are involved: S1. Synthesis of DTQ-COF The solid powder of 2,6-diaminoanthraquinone, i.e., DAAQ, and trialdehyde phloroglucinol, i.e., TFP, which has been pretreated, is transferred to a Pyrex tube, and then a mixed solution of mesitylene and N,N-dimethylacetamide is added to the Pyrex tube, and ultrasonic vibration is performed for 1-5 minutes to uniformly mix the solid powder and the mixed solution, and then acetic acid is added to continue ultrasonic vibration for 1-2 minutes; then the Pyrex tube is subjected to a freeze-vacuum process three times, flame-sealed with butane gas, and heated to obtain a brown-yellow powdery solid product; the solid product is washed 3-5 times by high-speed centrifugation with an acetone solution until the color of the washing solution becomes clear; the washed solid product is vacuum dried to obtain a brown-yellow solid powder DTQ-COF; S2. Preparation of PW 12 / DTQ-COF and PMo 12 / DTQ-COF Keggin type phosphotungstic acid, PW 12 , or Keggin-type phosphomolybdic acid, PMo 12 , stirred and dissolved in anhydrous ethanol to obtain Keggin type phosphotungstic acid, namely PW 12 , or Keggin-type phosphomolybdic acid, PMo 12 ethanol solution, then dissolve DTQ-COF in the above solution, stir for 20-24 h and filter, and vacuum dry the solid obtained after filtration to obtain PW 12 / DTQ-COF or PMo 12 / DTQ-COF; S3. Preparation of modified diaphragm (1) Dry grinding: PW 12 / DTQ-COF or PMo 12 / DTQ-COF was mixed with PVDF and Super-P, respectively, and the mixture was obtained after ball milling; (2) Wet grinding: Add NMP solution to the mixture and ball mill for 1-2 h to obtain a slurry; (3) The slurry is evenly coated on the PP surface using a 40-50 mm four-sided sampler, and then vacuum dried to obtain a diaphragm; (4) The diaphragm was cut into discs with a diameter of 16 mm to obtain a modified diaphragm.

2. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for a lithium-sulfur battery according to claim 1, characterized in that: The pretreatment in step S1 is specifically as follows: 2,6-diaminoanthraquinone, namely DAAQ, and trialdehyde phloroglucinol, namely TFP, are mixed and ground for 1-1.5 min, then 3-5 drops of ethanol are added, and ground again for 1-1.5 min to obtain a solid powder; The molar ratio of the 2,6-diaminoanthraquinone to trialdehyde pyrogallol is 8:(5-6).

3. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries according to claim 1, characterized in that: The volume ratio of mesitylene to N,N-dimethylacetamide in step S1 is 1:(2-4).

4. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for a lithium-sulfur battery according to claim 1, characterized in that: The usage ratio of 2,6-diaminoanthraquinone and N,N-dimethylacetamide in step S1 is: (15-20) mg: (0.3-0.6) ml.

5. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries according to claim 1, characterized in that: In step S1, the concentration of acetic acid is 6 mol / L, the amount of acetic acid used is 0.1-0.4 ml, the heating time is 100-150 h, and the heating temperature is 100-150 °C.

6. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries according to claim 1, characterized in that: The Keggin type phosphotungstic acid, i.e. PW 12 , or Keggin-type phosphomolybdic acid, PMo 12 The ratio of the mass of to the mass of DTQ-COF is (1-2):

10.

7. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries according to claim 1, characterized in that: In step S3 (1), the PW 12 / DTQ-COF or PMo 12 The mass ratio of / DTQ-COF, PVDF and Super-P is 6:1:3, and the ball milling time is 1-1.5 h.

8. The method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries according to claim 1, characterized in that: The vacuum drying temperature in all steps is 80-100°C, and the drying time is 12-24 h.

9. A modified diaphragm, prepared by the method for preparing a polyacid-modified covalent organic framework modified diaphragm for lithium-sulfur batteries according to claim 1.

10. A lithium-sulfur battery comprising the modified separator according to claim 9.

Citation Information

Patent Citations

  • Method for improving performance of COFs (Covalent Organic Frameworks) material used as electrode active material

    CN107180968A

  • Quinoquinonyl-based covalent organic framework material as well as preparation method and application thereof

    CN111333852A